Pengaruh Elemen Interior Zangrandi Ice Cream Surabaya terhadap Pengalaman Nostalgia Pengunjung - Fausta Ottoni Sasi; Sriti Mayang Sari; Celline Junica Pradjonggo (Intra, 2019)
Nostalgic experience is one of the ways to attract visitors to choose the desired space. The nostalgia experience itself is the emergence of a